Prevalence and factors affecting anxiety and depression among adult people with physical disabilities in Saudi Arabia: a cross-sectional study - Khalil A. Saleh; Waled A. M. Ahmed; Habib Alrashedi; Sameer A. Alkubati; Sameer A. Alkubati; Mokhtar Abdu Almoliky; Mokhtar Abdu Almoliky; Gamil Ghaleb Alrubaiee; Gamil Ghaleb Alrubaiee; Talal Ali Hussein Alqalah; Talal Ali Hussein Alqalah; Galal Faisal Albani; et al. (Frontiers in Psychology)
IntroductionAnxiety and depression are among the major challenges that influence the health of individuals, especially those with disabilities. This study aimed to assess the level of anxiety and depression and the factors that affect them among adult individuals with physical disabilities in Hail, Saudi Arabia.MethodsA descriptive cross-sectional study recruited 155 adult individuals with physical disabilities in the Hail region of Saudi Arabia. From January to May 2024, data were collected from people with disabilities using an online validated questionnaire based on the satisfaction and the HADS. The survey was sent to people with physical disabilities through the responsible bodies after being given the required permissions. The data were collected using a self-reported questionnaire.ResultsThe research included individuals between 20 and 40 years old, nearly half of whom (47.7%) were women. More than half of the participants were under 25 years old, and 80% of them complained of physical disability, which was mild (62.6%) and due to congenital causes (61.9%). The study findings also showed that 61.8% of people with physical disabilities was satisfied with the provided healthcare services and 32.9 and 18% of them reported high levels of anxiety and depression, respectively. Anxiety was significantly associated with the educational level, degree of disability, presence of chronic illnesses, and parking availability p < 0.05. Depression was significantly associated with the degree, cause, period of disability, the ability to visit the hospital alone, and the priority in the waiting area (p < 0.05). These associations were uncertain in correlation linear regression analysis, since moderate disabilities were significant predictors of anxiety and depression while other factors were not significantly associated.DiscussionThe majority of people with disabilities in Hail, Saudi Arabia complain of borderline to abnormal levels of anxiety compared with one-third of participants in the aspect of depression. Education, degree, type, cause of disability, and presence of chronic diseases had a significant impact on mental health among people with disabilities.